Penerapan Aplikasi Tawk To IduHelp! Sebagai Sarana Pelayanan Informasi di Perguruan Tinggi - Febriyanto, Erick; Rais, Nurlaila Suci Rahayu; Syafaah, Fikrah (Technomedia Journal, 2019)
Technological advances are running very quickly and have a great effect on human life, one of them in the world of education and activities. The rapid information technology, making the educational institutions also raise the standard facilities of information service system for students who are usually called Tawk.to. Tawk.to itself is an online chat feature on iDuHelp! which serves as an information service at Higher Education Raharja which can be accessed online anywhere by using Rinfo and greatly facilitate students if there are obstacles in the lecture. In the previous service is still using the method of chatting is still simple and still many obstacles that are difficult diminimalisirkan but with it the Tawk To this information service in Higher Education Raharja be very good. In this information service system not only can serve information about ilearning but this service can also help to serve constraint about system of Higher Education experienced by University Students. This paper presents an iDuHelp comparison! by using Tawk To and with iDuHelp! using a simple chat. With the study of Tawk To iDuHelp! this is expected to be a solution for students who have difficulty in lecture in terms of akdemik or any other facilities about Raharja Higher Education. Keywords: iDuHelp!, Information Services, Tawk To.